2016
DOI: 10.1016/j.clim.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-mediated immune responses in intestinal macrophages; implications for mucosal immunity and autoimmune diseases

Abstract: Monocytes are precursors of macrophages and key players during inflammation and pathogen challenge in the periphery, whereas intestinal resident macrophages act as innate effector cells to engulf and clear bacteria, secrete cytokines, and maintain intestinal immunity and homeostasis. However, perturbation of toll-like receptor signaling pathway in intestinal macrophages has been associated with tolerance breakdown in autoimmune diseases. In the present review, we have summarized and discussed the role of toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 162 publications
(182 reference statements)
0
12
0
Order By: Relevance
“…If so, multiple microbial products such as RNA, DNA, peptidoglycan and flagellin derived from bacteria, viruses, fungi and other gastrointestinal residents may translocate into systems and cause systemic immune activation [5355]. Indeed, our recent work shows that monocytes were activated in vivo in women compared to men, and plasma level of soluble CD14, a marker of monocyte activation by LPS, was higher in women relative to men [56], suggesting a role of systemic bacterial products in immune activation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…If so, multiple microbial products such as RNA, DNA, peptidoglycan and flagellin derived from bacteria, viruses, fungi and other gastrointestinal residents may translocate into systems and cause systemic immune activation [5355]. Indeed, our recent work shows that monocytes were activated in vivo in women compared to men, and plasma level of soluble CD14, a marker of monocyte activation by LPS, was higher in women relative to men [56], suggesting a role of systemic bacterial products in immune activation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the microbiota is critical for induction of intestinal regulatory T cells (Tregs) as they are absent in germ-free mice (Atarashi et al, 2011). Disrupted signaling downstream from the microbiota, such as through loss of toll-like receptor pathways, is thought to drive disease pathology including in IBD (Zhou et al, 2016). We and others have found that the microbiota is required for proper intestinal barrier repair through innate lymphoid cell production of IL-22 (Longman et al, 2014; Ouyang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, a key host-defense cell type, recognize invading pathogens via pathogen-associated pattern recognition receptors to initiate anti-infection innate immune responses [ 1 ]. During Mycobacterium tuberculosis ( M. tuberculosis ) infection, Toll-like receptors (TLRs) on the surface of macrophages are shown to recognize pathogens, trigger endocytosis to form phagosomes, produce cytokines, improve cell apoptosis, and thus exert bactericidal activities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%